2015
DOI: 10.1111/socf.12149
|View full text |Cite
|
Sign up to set email alerts
|

Becoming a (Pan)ethnic Attorney: How Asian American and Latino Law Students Manage Dual Identities

Abstract: Managing professional and personal identities often belabor upwardly mobile racialized individuals. I examine in this article how Asian American and Latino law students negotiate (pan)ethnic identities while learning to become lawyers. I contend that managing dual identities creates (pan)ethnic duty among Asian American and Latino law students. I focus on those planning to work in law firms, at least initially. While there are many career options for law students, most, irrespective of race, pursue initial car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…These racialization processes in schooling continue as students transition to college where many develop a stronger sense of ethnic consciousness, especially on campuses where they are the minority (Feliciano 2009; Tovar and Feliciano, 2009; Umaña-Taylor 2004). Yung-Yi Diana Pan (2015) argues this process occurs among Asian and Latino law students, as they become more race-conscious and aware of their panethnic unity while in predominantly White law school.…”
Section: Literature Reviewmentioning
confidence: 99%
“…These racialization processes in schooling continue as students transition to college where many develop a stronger sense of ethnic consciousness, especially on campuses where they are the minority (Feliciano 2009; Tovar and Feliciano, 2009; Umaña-Taylor 2004). Yung-Yi Diana Pan (2015) argues this process occurs among Asian and Latino law students, as they become more race-conscious and aware of their panethnic unity while in predominantly White law school.…”
Section: Literature Reviewmentioning
confidence: 99%
“…For example, Waters (1999) found that despite West Indian New Yorkers’ assertion as Trinidadian, Guyanese, or Jamaican, their skin color and phenotype resulted in their racialized ascription as black. And scholars of race and ethnicity claim that panethnicity formation occurs through a process of racialization reinforced by external forces in concert with the mobilization of a common identity by insiders (Brown and Jones 2015; Pan 2015; Pan 2017a, 2017b; Reyes 2017, 2018).…”
Section: Literature Reviewmentioning
confidence: 99%